The Effect of TEACCH Method towards Self-Help Ability on Wearing Clothes for Children with Down Syndrome - Ismanura Firdaus; Ahmad Samawi (Department of Special Education, 2019)
Children with Down syndrome have intellectual delay in their coginitive development. One of the characteristics is the low ability of self-development. The aim of this research is to describe the effect of the TEACCH method towards the ability of self-help on wearing clothes for down syndrome students. The research was arranged based on the Single Subject Research (SSR) experimental method with the A-B-A design. The conclusion of this research is that the intervention using the TEACCH method can establish the ability to wear clothes of Down syndrome students.